The multidimensional ionotropic receptors of Drosophila melanogaster. Issue 1 (31st August 2017) - Rimal, S.; Lee, Y.
Abstract: Ionotropic receptors (IRs), which form ion channels, can be categorized into conserved 'antennal IRs', which define the first olfactory receptor family of insects, and species‐specific 'divergent IRs', which are expressed in gustatory receptor neurones. These receptors are located primarily in cell bodies and dendrites, and are highly enriched in the tips of the dendritic terminals that convey sensory information to higher brain centres. Antennal IRs play important roles in odour and thermosensation, whereas divergent IRs are involved in other important biological processes such as taste sensation. Some IRs are known to play specific biological roles in the perception of various molecules; however, many of their functions have not yet been defined. Although progress has been made in this field, many functions and mechanisms of these receptors remain unknown. In this review, we provide a comprehensive summary of the current state of knowledge in this field.